The Victory of Pluralism: The Role of International Law in The South China Sea Dispute - Verdinand Robertua Siahaan (Sospol : Jurnal Sosial Politik, 2017)
AbstractThis research discussed the role of Permanent Court of Arbitration’s decision on the dynamic of South China Sea dispute. Court’s decision in July 2016 to regulate South China Sea based on UNCLOS’s regulation has provoked China’s objection. This research question is on how to understand the role of international law in the South China Sea dispute using English School Theory. To answer the research question, this research is using English School Theory with its two pillars namely pluralism and solidarism. This research shows two findings. First, the PCA decision has been used by the Philippines to be momentum for transformation from solidarist mode of foreign policy to pluralist mode. Secondly, the pluralism pillar of English School is more relevant in analyzing the role of international law on South China Sea Dispute.Key words: English School, international law, Permanent Court of Arbitration, pluralism, solidarism, South China Sea AbstrakPenelitian ini membahas peran Permanent Court of Arbitration (PCA) di dalam resolusi konflik Laut Tiongkok Selatan (LTS). Keputusan PCA yang menggunakan UNCLOS sebagai tata kelola LTS memprovokasi kemarahan Tiongkok. Pertanyaan penelitian ini adalah bagaimana memahami peran hukum internasional dalam konflik Laut Tiongkok Selatan menggunakan teori English School. English School dengan kedua pilarnya pluralisme dan solidarisme menjadi pisau analisis utama untuk menjawab pertanyaan penelitian. Penelitian ini menghasilkan dua kesimpulan. Pertama, keputusan PCA digunakan sebagai Filipina sebagai momentum transformasi kebijakan luar negeri Filipina dari solidarisme menjadi pluralisme. Kedua, pilar pluralisme lebih relevan menjelaskan peran hukum internasional dalam sengketa Laut Tiongkok Selatan.Kata kunci: English School, hukum internasional, Laut Tiongkok Selatan, Permanent Court of Arbitration, pluralisme, solidarisme